Control of Formin Distribution and Actin Cable Assembly by the E3 Ubiquitin Ligases Dma1 and Dma2. Issue 1 (1st September 2016) - Juanes, M Angeles; Piatti, Simonetta
Abstract: Formins are widespread actin-polymerizing proteins that play pivotal roles in a number of processes, such as cell polarity, morphogenesis, cytokinesis, and cell migration. In agreement with their crucial function, formins are prone to a variety of regulatory mechanisms that include autoinhibition, post-translational modifications, and interaction with formin modulators. Furthermore, activation and function of formins is intimately linked to their ability to interact with membranes. In the budding yeast Saccharomyces cerevisiae, the two formins Bni1 and Bnr1 play both separate and overlapping functions in the organization of the actin cytoskeleton. In addition, they are controlled by both common and different regulatory mechanisms. Here we show that proper localization of both formins requires the redundant E3 ubiquitin ligases Dma1 and Dma2, which were previously involved in spindle positioning and septin organization. In dma1 dma2 double mutants, formin distribution at polarity sites is impaired, thus causing defects in the organization of the actin cable network and hypersensitivity to the actin depolymerizer latrunculin B. Expression of a hyperactive variant of Bni1 ( Bni1 - V360D ) rescues these defects and partially restores proper spindle positioning in the mutant, suggesting that the failure of dma1 dma2 mutant cells to position the spindle is partly due to faulty formin activity. Strikingly, Dma1 /2 interact physically with both formins, while their ubiquitin-ligase activity is required for formin function and polarized localization. Thus, ubiquitylation of formin or a formin interactor(s) could promote formin binding to membrane and its ability to nucleate actin. Altogether, our data highlight a novel level of formin regulation that further expands our knowledge of the complex and multilayered controls of these key cytoskeleton organizers.